Kalman Filter: Historical Overview and Review of Its Use in Robotics 60 Years After Its Creation - Urrea-Onate, E; Agramonte-Alburquerque, R (Hindawi Limited, 2021)
Due to its widespread application in the robotics field, the Kalman filter has received increased attention from researchers. This work reviews some of the modifications conducted on to this algorithm over the last years. Problems such as the consistency, convergence, and accuracy of the filter are also dealt with. Sixty years after its creation, the Kalman filter is still used in autonomous navigation processes, robot control, and trajectory tracking, among other activities. The filter is not only restricted to robotics but is also present in different fields, such as economics and medicine. In addition, the characteristics of each modification on this filter are analyzed and compared. © 2021 Claudio Urrea and Rayko Agramonte.